Pemanfaatan Data Kependudukan Dalam Perencanaan Kelurahan Kedung Baruk - Agustina, Nia Giant Virnanda; Yusuf Hariyoko (Policy and Maritime Review, 2024)
In the process of changing the order of society's life towards a better one through development. The development process involves many factors and is interconnected, so organized planning is needed from administrative readiness to plans or concepts for development. In preparing development plans to determine policy direction and goals, accurate and accountable population data is needed, so that the use of population data can achieve the planned goals. Population data contains population registration and other important events summarized in the Population Administration Information System. This research discusses using population data to achieve state goals, namely community welfare. However, population data does not completely match the reality of local residents, so it is supported by survey results by local government officials. The research uses a descriptive method with a qualitative approach to obtain information to complete this research